2020
DOI: 10.1038/s41467-020-14305-0
|View full text |Cite
|
Sign up to set email alerts
|

Electronic parameters in cobalt-based perovskite-type oxides as descriptors for chemocatalytic reactions

Abstract: Perovskite-type transition metal (TM) oxides are effective catalysts in oxidation and decomposition reactions. Yet, the effect of compositional variation on catalytic efficacy is not well understood. The present analysis of electronic characteristics of B-site substituted LaCoO 3 derivatives via in situ X-ray absorption spectroscopy (XAS) establishes correlations of electronic parameters with reaction rates: TM t 2g and e g orbital occupancy yield volcanotype or non-linear correlations with NO oxidation, CO ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
58
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(61 citation statements)
references
References 52 publications
1
58
2
Order By: Relevance
“…It is well known that the activation of surface lattice oxygen plays a key role in various oxygen related catalytic reactions for transition metal oxide catalysts. [46][47][48] The active lattice oxygen not only decreases the activation energy barrier of the transition from O 2 − species to important intermediate O 2 2− species in the activation process of oxygen molecule, but also improves the catalytic efficiency of lattice oxygen involved in the rection. [45,49,50] As displayed in Figure 6, in the O 2 dissociation pathway, the two steps for O 2 →O 2 − and O 2 2− → O − are exothermic reactions and the relative energy is negative, and they have only a small effect on the catalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…It is well known that the activation of surface lattice oxygen plays a key role in various oxygen related catalytic reactions for transition metal oxide catalysts. [46][47][48] The active lattice oxygen not only decreases the activation energy barrier of the transition from O 2 − species to important intermediate O 2 2− species in the activation process of oxygen molecule, but also improves the catalytic efficiency of lattice oxygen involved in the rection. [45,49,50] As displayed in Figure 6, in the O 2 dissociation pathway, the two steps for O 2 →O 2 − and O 2 2− → O − are exothermic reactions and the relative energy is negative, and they have only a small effect on the catalytic process.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies have reported electronic parameters (e g orbital occupancy) of inorganic perovskites as the descriptor for catalytic activity in catalytic reactions. 7,14 The low surface areas obtained herein will not be used as sole descriptor for…”
Section: Characterizationmentioning
confidence: 99%
“…Moreover, perovskites with an e g orbital filling and a number of oxygen vacancies can be used as oxygen evolution reduction (OER) catalysts. 3,14 There are a number of synthetic methods which can be used to synthesize perovskites including micro-emulsion, 15 soft template, 16 freeze-drying, 12 nanocasting (hard template), 17 and hydrothermal synthesis. 18 Perovskites synthesized by solgel method provide materials that are crystalline and with high purity when compared to other methods.…”
Section: Introductionmentioning
confidence: 99%
“…In this case the spin state is very sensitive to changes in the coordination geometry, e.g., Co-O length or Co-O-Co angle. Different to the cobalt, in manganese oxides Mn 3+ always remains in high-spin state (M S = 4µ B ) [18].…”
Section: Introductionmentioning
confidence: 98%